Mitochondrial NADPH dehydrogenase B1 negatively regulates Arabidopsis tolerance to drought stress through affecting ABA-triggered stomatal closure - Wei, Jinxin (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025. Published by Elsevier Masson SAS.